The extravascular implantable cardioverter-defibrillator: characterization of anatomical parameters impacting substernal implantation and defibrillation efficacy. Issue 5 (18th October 2021) - Molnár, Levente; Crozier, Ian; Haqqani, Haris; O'Donnell, David; Kotschet, Emily; Alison, Jeffrey; Thompson, Amy E; Bhatia, Varun A; Papp, Roland; Zima, Endre; Jermendy, Ádám; Apor, Astrid; et al.
Abstract: Aims: The aim of this study is to provide a thorough, quantified assessment of the substernal space as the site of extravascular implantable cardioverter-defibrillator (ICD) lead placement using computed tomography (CT) scans and summarizing adverse events and defibrillation efficacy across anatomical findings. Subcutaneous ICDs are an alternative to transvenous defibrillators but have limitations related to ICD lead distance from the heart. An alternative extravascular system with substernal lead placement has the potential to provide defibrillation at lower energy and pacing therapies from a single device. Methods and results: A multi-centre, non-randomized, retrospective analysis of 45 patient CT scans quantitatively and qualitatively assessing bony, cardiac, vascular, and other organ structures from two human clinical studies with substernal lead placement. Univariate logistic regression was used to evaluate 15 anatomical parameters for impact on defibrillation outcome and adjusted for multiple comparisons. Adverse events were summarized. Substernal implantation was attempted or completed in 45 patients. Defibrillation testing was successful in 37 of 41 subjects (90%) using ≥10 J safety margin. There were two intra-procedural adverse events in one patient, including reaction to anaesthesia and an episode of transient atrial fibrillation during ventricular fibrillation induction. Anatomical factors associated with defibrillation failure included large rib cage width, myocardium extending very posteriorly, and a low heart position in the chest ( P -values <0.05), though not significant adjusting for multiple comparisons. Conclusion: Retrospective analysis demonstrates the ability to implant within the substernal space with low intra-procedural adverse events and high defibrillation efficacy despite a wide range of anatomical variability.